The investigation into the physicochemical properties of fermented soybean meal and its effects as a substitute for soybean meal on the growth performance and intestinal development of broiler chickens - Manqi Zhao; Xing Chen; Shuang Li; Guohua Liu; Zhimin Chen; Peilong Yang; Kun Meng; Aijuan Zheng (Poultry Science)
This experiment aims to investigate the physicochemical properties of fermented soybean meal (FSBM) and its effects on the growth and development of broilers when used as a substitute for soybean meal (SBM). The process optimization of FSBM was based on indicators such as particle size, moisture content, temperature, and the amounts of protease and microbial agents added. The physicochemical indicators of the FSBM meal were measured accordingly. On this basis, 320 one-day-old AA broilers were randomly divided into 4 treatment groups, with each group having 8 replicates. The treatment groups were: control (CON) group was fed a basal diet. The experimental group replaced 5 % (FSBM-1), 7.5 % (FSBM-2), and 10 % (FSBM-3) of SBM with FSBM. The trial period lasted for 42 d. The results indicate that the crude protein (CP) and acid-soluble protein (ASP) content of FSBM have significantly increased. Additionally, the amino acid content of FSBM surpasses that of SBM. Furthermore, the peak area percentage (PAP), number average molecular weight (NAMW), and weight average molecular weight (WAMW) for molecules below 5000 Da have shown significant increases (P<0.05). FSBM also significantly reduces anti-nutritional factors, including raffinose, stachyose, glycinin, etc. In the broiler chicken experiment, the ADG of the FSBM-1 group from 22 to 42 d and from 1 to 42 d was significantly increased (P<0.05), while the F/G was significantly reduced (P<0.05). Additionally, compared to the CON group, the nutrient apparent metabolism rates of dry matter (DM), crude protein (CP), and energy (EN) in the diet were also significantly enhanced (P<0.05). The comparison of broiler chickens in the FSBM-1 group at 21 d and 42 d shows a significant decrease (P<0.05) in the crypt depth (CD), while the villus height to crypt depth (V/C) significantly increased (P<0.05). In summary, fermentation can significantly reduce the anti-nutritional factors present in SBM and enhance feed quality. Replacing 5% of SBM with FSBM can notably improve the growth performance and intestinal morphology of broiler chickens.